2005
DOI: 10.1007/s10393-004-0139-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Climate Change on Lyme Disease Risk in North America

Abstract: An understanding of the influence of climate change on Ixodes scapularis, the main vector of Lyme disease in North America, is a fundamental component in assessing changes in the spatial distribution of human risk for the disease. We used a climate suitability model of I. scapularis to examine the potential effects of global climate change on future Lyme disease risk in North America. A climatebased logistic model was first used to explain the current distribution of I. scapularis in North America. Climate cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
188
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(210 citation statements)
references
References 45 publications
7
188
0
2
Order By: Relevance
“…More generally, it is widely accepted that the distribution and dynamics of vector-borne infections are particularly sensitive to climatic conditions, by virtue of the sensitivity of the (arthropod) vectors themselves to variations in temperature, humidity, and often quantities of standing water used as breeding sites. This work has been dominated by mosquito-borne infections such as malaria and dengue and by tick-borne infections such as Lyme disease and tick-borne encephalitis (22)(23)(24)(25). Much less attention has been focused on flea-borne infections or on direct effects on the (vertebrate) wildlife reservoirs.…”
Section: Resultsmentioning
confidence: 99%
“…More generally, it is widely accepted that the distribution and dynamics of vector-borne infections are particularly sensitive to climatic conditions, by virtue of the sensitivity of the (arthropod) vectors themselves to variations in temperature, humidity, and often quantities of standing water used as breeding sites. This work has been dominated by mosquito-borne infections such as malaria and dengue and by tick-borne infections such as Lyme disease and tick-borne encephalitis (22)(23)(24)(25). Much less attention has been focused on flea-borne infections or on direct effects on the (vertebrate) wildlife reservoirs.…”
Section: Resultsmentioning
confidence: 99%
“…29,49 Some researchers have speculated that increases in tick-borne diseases may be fueled by ecologic or climate changes, 50,51 and an increase in actual disease is clearly supported by some focal patterns of recent RMSF emergence. 25 However, the findings from our study suggest that the increase in reported RMSF incidence further involves a complex interplay of physician awareness, diagnostic practices, and reporting policies.…”
Section: Discussionmentioning
confidence: 99%
“…Brownstein et al used a climate-based suitability model to forecast the effect of climate change on I. scapularis expansion in Canada [42]. These authors assumed that established populations of blacklegged ticks were limited to a small number of foci in southern Ontario, but their assertions are unverifiable.…”
Section: Climate Change Projectionsmentioning
confidence: 99%
“…Ironically, blacklegged ticks were already in central Canada prior to 1970 [34]. Since the benchmark parameters are incorrect, forecasts of a 213% increase in I. scapularis foci further north in Canada by the 2080s [42], are misleading. Moreover, any studies on ticks and climate change have been inconclusive.…”
Section: Climate Change Projectionsmentioning
confidence: 99%